Welcome to the Journal of Casting and Materials Engineering - Grabowska, Beata (Journal of Casting & Materials Engineering, 2017)
The idea of a new journal emerged within the Circle of the Polish Foundrymen’s Association (Stowarzyszenia Techniczne Odlewników Polskich – STOP), a group of scientists operating in the Faculty of Foundry Engineering at the AGH University of Science and Technology.